Mapping legitimacy discourses in democratic nation states: Great Britain, Switzerland, and the Unites States compared - Achim Hurrelmann; Zuzana Krell-Laluhová; Steffen Schneider (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
This working paper first outlines the contours of a discourse analytical approach to the study of legitimation processes and then presents findings from a quantitative analysis of legitimacy-related communication in selected print media of the United Kingdom, Switzerland, and the United States in 2004. Our data suggest considerable differences between the three countries with regard to levels of (de)legitimation, privileged legitimation resources, and legitimation styles. The micro dynamics of legitimation processes in 2004 were characterised by nationally specific legitimation attention cycles. References to internationalisation and deparliamentarisation - two trends that are often held responsible for a severe legitimacy crisis of the nation state and representative democracy - play no more than a marginal role in legitimacy discourses. We conclude that evidence for a pervasive and full-fledged erosion of the nation state's legitimacy - or a uniform shift from input to output legitimation - is scant. – – Das Arbeitspapier skizziert die Grundzüge eines diskursanalytischen Ansatzes für die Untersuchung von Legitimationsprozessen und präsentiert Ergebnisse einer quantitativen Analyse der legitimationsrelevanten Kommunikation, die im Jahr 2004 in ausgewählten Printmedien aus Großbritannien, der Schweiz und den USA veröffentlicht wurde. Es zeigen sich deutliche Unterschiede zwischen den drei Ländern hinsichtlich des Ausmaßes von legitimierenden bzw. delegitimierenden Stellungnahmen, hinsichtlich der jeweils eingesetzten Legitimationsressourcen und der vorherrschenden Legitimationsstile. Die Mikrodynamik von Legitimationsprozessen ist durch national spezifische - Legitimations-Aufmerksamkeits-Zyklen - gekennzeichnet. Bezugnahmen auf Internationalisierung und Deparlamentarisierung - zwei Entwicklungen, die häufig als Ursachen für eine ernstliche Legitimationskrise des Nationalstaats bzw. der repräsentativen Demokratie angesehen werden - spielen in den untersuchten Legitimationsdiskursen nur eine untergeordnete Rolle. Für eine weitreichende Erosion nationalstaatlicher Legitimität - oder auch nur für eine systematische Verschiebung von input- hin zu output-orientierten Legitimationsargumenten - finden sich keine Anzeichen.
Keywords: 300; Demokratie; Parlamentarismus; Nationalstaat; Vergleich; Großbritannien; Schweiz; USA; Legitimität